A New Load Detection Method and Circuit Analysis for Quasi Resonant Inverter - Zungor, Fatih; Emre, Burhaneddin; Oz, Baris; Ozturk, Metin (IEEE, 2021)
Induction Heating (III) technology is very popular in-home usage due to its safety, efficiency, and fast heating advantages. Although common induction heaters are designed to heat ferromagnetic pans, it is not easy to determine load conditions in every working condition. Because of the relationship between inverter circuit parameters and induction loads, load identification methods are very critical in induction hob applications. On the other hand, circuit elements (e.g., capacitor, inductor, frequency, etc.) are very important not only for the accurate power control but also reliability to design an induction hob. This study focuses on a new load detection method based on circuit analysis for quasi resonant induction hobs. Proposed method is theoretically examined and proven by the help of simulations and prototyped circuit.
Keywords: Home appliances; induction cooking systems; induction cookers; load detection methods; resonant converters; single switch quasi resonant inverter; INDUCTION; IDENTIFICATION; CONVERTER; EFFICIENT; Science & Technology - Other Topics; Energy & Fuels